Development of political leadership skills in Panamanian children through the virtual program: Niño Presidente - Ramirez, Michelle; Rodriguez Otero, Victoriano (Southern perspective / Perspectiva austral, 2024)
From infancy, we absorb influences from our caregivers and environment that shape us. As we grow up, these stimuli shape our future decisions, from financial matters to our political participation. Early understanding of the consequences of our actions makes us more conscientious citizens. It is essential to educate children in moral values and in their ability to be agents of change in society. The "Child President" model proposes to teach children from a young age about their rights and responsibilities, enabling them to address real problems with creativity and leadership